2013
DOI: 10.1108/19348831311322515
|View full text |Cite
|
Sign up to set email alerts
|

Contextual influences on leadership in emergency type organisations

Abstract: Purpose -The purpose of this paper is to further the theoretical understanding of leadership in emergency type organisations by modelling contextual aspects which are assumed to influence it. Design/methodology/approach -A theoretical analysis followed by an operationalisation of key concepts and two small-scale empirical cross-sectional tests. Findings -Contextual conditions at the group, organisation, and environmental levels that are assumed to influence leadership in emergency type organisations were model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…The interviews consisted of broad open-ended questions and individually adapted follow-up questions. The interview themes were inspired by the model developed by Larsson and The armed forces The police Hyllengren (2013) and the informants were specifically asked to reflect upon the following themes:…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interviews consisted of broad open-ended questions and individually adapted follow-up questions. The interview themes were inspired by the model developed by Larsson and The armed forces The police Hyllengren (2013) and the informants were specifically asked to reflect upon the following themes:…”
Section: Data Collectionmentioning
confidence: 99%
“…A previous study (Larsson and Hyllengren, 2013) identified a number of contextual conditions affecting leadership in stressful missions of civilian and military first responders. These included: environmental aspects such as dynamic stressors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, recent literature has given special attention on the importance of emergency leadership in organizational resilience (Hills, 2015;De Florio, 2014;Moe, 2012), as well as contextual aspects of leadership (Charman, 2015;Larsson and Hyllengren, 2013). Yet, there appears to be a paucity of literature that examines emergency leadership challenges from a strategic systems perspective (Caro, 2015;Karaca et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The literature stresses the importance of leadership in inspiring and fostering mutual respect, open interprofessional communication, collaborative decision-making, all of which motivate a commitment to high quality systems of care. [27][28][29][30][31] Urby and McEntire (2015) [32] have underscored that transformational leaders are change agents that form the backbone of high-performing and effective systems that result in positive outcomes, such as lower mortality and morbidity rates, greater community resilience, higher quality of care. [33][34][35][36][37][38] 1.2 Holonic paradigms in emergency management systems This study proposes a holonic perspective of emergency leadership in the context of complex adaptive emergency management systems.…”
Section: Transformational Emergency Systems Leadershipmentioning
confidence: 99%